Seroprevalence and risk factors of bovine neosporosis in the valley in the Mantaro Valley, Junín, Peru - Arauco Villar, Fernando (2018)
The seroprevalence of bovine neosporosis in dairy herds in four provinces of the Mantaro Valley, Peru and the main risk factors involved, through the ELISA test were determined. Blood samples were taken from 425 animals in 37 herds and an epizootic survey was applied in parallel. The general sample prevalence for bovine neosporosis was 15.3%, the prevalence per herd was 12.8% and the herd prevalence was 56.8%, without significant differences between provinces. The massive and constant presence of rats (OR: 18,417), inadequate health management (OR: 7.5) and inadequate personnel management (OR: 12.75) were identified as risk factors for the presentation of neosporosis. An association was found between high prevalence of neosporosis with the presence of repeat breeder cows in the herd, with cases of abortions and anomalous births, and with the use of water from ditches and wells for drinking.